Aplikasi Komposit Polimer Berpenguat Serat Untuk Perbaikan Pipa Kondisi Resiko Rendah Melalui Pengembangan Perangkat Lunak - Hermawan Judawisastra; Sella Aprilia Irawan (Badan Kerja Sama Pendidikan Metalurgi dan Material (BKPMM), 2018)
Failure and leakage might occurs on pressurized component such as piping or pipeline. The combination of probability of piping failure with consequence may result in low risk condition. The condition still need to be repaired. Steel patching is common to be used for pipe repair with some limitation. The use of fiber-reinforced plastic composites offers some advantages i.e. for inaccessible and unsafe pressurized pipe conditions, easily repaired, and highly corrosion resistance compared to metal. The huge variety of composite characteristics requires high number of data collection and evaluation for determination of patching composite data. This research aims to develop a software to facilitate repair process using composites. The development of the software is based on ASME PCC 2, build using Microsoft Visual Studio and C# programming language. Validation of flowchart and case studies are performed to test the algorithm. The results of software calculation are compared with excel calculation. The software has been successfully created, validated and can be used to repair pipe in low risk condition using composite fiber reinforced polymer. Pipe repair in low risk condition using composite is affected by operating temperature, operating pressure, type of fluid, and composite strength. The thickness of composite patching is affected by pipe diameter, depth of external corrosion defect, location of corrosion defect, and risk category.